THE EXISTENCE OF THE IQRA METHOD IN OVERCOMING ILLITERACY OF THE QURAN AT ULIL ALBAB TPA LEMBANG VILLAGE EAST BANGGAE DISTRICT - Akhmad Akhmad; Andi Abd Muis; Muhammad Sabir; Amiruddin Amiruddin; Ansar Ansar; Salpiana Salpiana (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to find out the description of the existence of the Iqra' Method in Overcoming Al-Qur'an Illiteracy at the Lembang Village TPA, to find out the influence of the Iqra' Method in Overcoming Al-Qur'an Illiteracy at the Lembang Village TPA, to find out the challenges faced by Koran Recitation teachers. Iqra' in Overcoming Al-Qur'an Illiteracy at Lembang Village TPA. The type of research used was qualitative (Field Research) which was carried out at the Lembang Village TPA, Research approach: Qualitative Descriptive. Primary data sources (Qur'an teachers and students), secondary data (Documents). Research instruments: observation guidelines, interview guidelines and documentation guidelines. Data collection procedures: observation, interviews and documentation. Data analysis techniques: data reduction, data presentation, drawing conclusions and verification. Research results: 1) The Iqra' Method in Overcoming Al-Qur'an Illiteracy, most of the students can read the Koran, 2) The Iqra' Method is effective in Overcoming Al-Qur'an Illiteracy in Lembang Village.